Предмет: Математика,
автор: missisbessonov
6(3х + 5у) + 7х - 5у при х+у = 3
помогите, пожалуйста
Ответы
Автор ответа:
0
6(3х + 5у) + 7х - 5у =
= 18х + 30у + 7х - 5у =
= (18х + 7х) + (30у - 5у) =
= 25х + 25у = 25(х + у)
При х + у = 3
25 * 3 = 75
Ответ: 75.
= 18х + 30у + 7х - 5у =
= (18х + 7х) + (30у - 5у) =
= 25х + 25у = 25(х + у)
При х + у = 3
25 * 3 = 75
Ответ: 75.
Похожие вопросы
Предмет: Информатика,
автор: NeXoRT
Предмет: Английский язык,
автор: vjawer34343
Предмет: Химия,
автор: MariannaBliss
Предмет: Физика,
автор: karinakanoplya
Предмет: Литература,
автор: арина65